2020
DOI: 10.3390/ijms21228792
|View full text |Cite
|
Sign up to set email alerts
|

Changes in microRNA Expression in the Cochlear Nucleus and Inferior Colliculus after Acute Noise-Induced Hearing Loss

Abstract: Noise-induced hearing loss (NIHL) can lead to secondary changes that induce neural plasticity in the central auditory pathway. These changes include decreases in the number of synapses, the degeneration of auditory nerve fibers, and reorganization of the cochlear nucleus (CN) and inferior colliculus (IC) in the brain. This study investigated the role of microRNAs (miRNAs) in the neural plasticity of the central auditory pathway after acute NIHL. Male Sprague–Dawley rats were exposed to white band noise at 115 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
(45 reference statements)
0
10
0
1
Order By: Relevance
“…The sound stimuli applied were clicks at 4 and 16 kHz. The procedures were similar to those previously described ( Park et al., 2020 ). Mice were tested and monitored until recovery.…”
Section: Methodsmentioning
confidence: 99%
“…The sound stimuli applied were clicks at 4 and 16 kHz. The procedures were similar to those previously described ( Park et al., 2020 ). Mice were tested and monitored until recovery.…”
Section: Methodsmentioning
confidence: 99%
“…As short non-coding transcripts, miRNAs orchestrate the transcription or translation of genes during development and pathological conditions, including auditory deprivation [ 7 , 8 ]. As miRNAs are abundant in the central nervous system and harbor multiple target genes, they are thought to regulate the neural pathways of neurogenesis and synaptogenesis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent preclinical studies have reported that dynamic changes in miRNA expression contribute to hearing function [ 7 , 8 , 12 , 13 ]. miRNAs are presumed to regulate the development of hearing function [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on miRNAs have mostly focused on chronic noise-induced hearing loss models. However, a previous study measured miRNA expression in the cochlear nucleus and inferior colliculus, not the hippocampus, after acute noise exposure [ 12 ]. Since noise-induced hearing loss and related cognitive decline may progress slowly over a long period, early diagnosis and prevention are important.…”
Section: Introductionmentioning
confidence: 99%